Analysis of the anatomical lines of the medial nasal dorsum after use of spreader grafts in open rhinoplasty - Frederico Guilherme Lopes Silveira (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: First described by Sheen in 1984, the use of spreader grafts has become increasingly routine. Spreader grafts are indicated for recovery or maintenance of the internal nasal valve and correction of septum deviation with improvement in the anatomical lines of the nasal dorsum. This study avaluated the anatomical lines of the middle nasal third (MNT) of the nasal dorsum after the use of spreader grafts in open rhinoplasty. METHODS: A series of 17 patients who underwent rhinoplasty with the inclusion of spreader grafts between March 2013 and November 2014 were analyzed. Spreader grafts were removed from the septum or costal cartilage based on an anthropometric comparison between the medial intercanthal distance and the caudal width of the MNT. RESULTS: Spreader grafts were effective for septum correction without causing excessive enlargement in 12 patients (70.6%). Three patients (17.6%) had undesirable results with local bulging and 2 patients (11.8%) retained their pre-surgery non-standard measures. In the majority of cases (41.2%), there was a local increase of 3 mm, with a mean of increase of 2.67 mm. CONCLUSION: In the author's point of view, even in cases where there was bulging of the anatomical lines of the nasal dorsum, spreader grafts promoted long-lasting satisfactory results, and prevented open-roof deformities and stigmas inherent to the surgery itself.